VENOM CAUSATIVE MORPHOLOGY OR AS A VENEREAL DISEASE - Ubaydullayev Shohbozbek; Baxromov Bekjon; Samarov Asliddin (Western European Studies, 2024)
venereal or syphilis is a classic type of venereal disease, the causative agent of which is whitish Treponema, and this trigger can also damage organs other than the genitals. Zahm is transmitted through the genital tract. The disease is characterized by the occurrence and slow development of various fog clinical symptoms. If left untreated, venereal disease leads to serious changes in the internal organs and nervous system. Over the past years, the worldwide incidence of syphilis has increased 5-fold. The poison trigger is present in the patient's blood, skin wound, lymph nodes, spinal fluid, saliva, nerve tissue and all organs, even in the milk of a woman suffering from poison, and in male lust. Leakage treponema dies when dried outside the body, but lives long in a humid environment (e.g., lust, saliva, vaginal mucus).
Keywords: leakage treponema; venereal disease; congenital zahm